Gender-Specific Differences on the Association of Hypertension with Subclinical Thyroid Dysfunction - Jingkai Zhang; Chao Huang; Zhaowei Meng; Yaguang Fan; Qing Yang; Wenjuan Zhang; Yuxia Gao; Zhenwen Yang; Heng Cai; Bo Bian; Yongle Li; Xuefang Yu; et al. (International Journal of Endocrinology)
Objective. Both hypertension and subclinical thyroid dysfunction (STD) have high prevalence and clinical importance, but their relationship is still a matter of debate. We aimed to explore gender-specific difference on the association between hypertension and STD in Chinese. Methods. We recruited 13,380 ostensible healthy participants (8,237 men and 5,143 women). The associations between hypertension and STD were analyzed on a gender-based setting after dividing STD into subclinical hypothyroidism, subclinical hyperthyroidism and further subgrouped euthyroidism. Crude and adjusted odds ratios of STD for hypertension were analyzed by binary logistic regression. Results. An increasing trend of hypertension prevalence was found along with aging in both genders. Yet, higher male hypertension prevalence was found until 65 years, and then it intersected with female hypertension prevalence. Women had significantly higher propensity for STD than men. Yet, in elderly participants, this gender-specific difference became less obvious. We displayed detrimental effects for subclinical hypothyroidism in both genders after multiple-covariate adjustments, yet no such effects were shown for subclinical hyperthyroidism. Moreover, females with subclinical hypothyroidism were more likely to be associated with hypertension than males, and the corresponding odds ratios were 1.619 (P<0.01) and 1.557 (P<0.05), respectively. For systolic blood pressure, the adjusted odds ratios were 1.371 (P<0.05) and 1.154 (P>0.05), and for diastolic blood pressure, 1.604 (P<0.01) and 1.564 (P<0.01), respectively. Conclusion. We demonstrate that hypertension is associated with subclinical hypothyroidism, but not with subclinical hyperthyroidism. Moreover, females with subclinical hypothyroidism are more likely to be associated with hypertension than males.